Common Lespedeza (Kummerowia striata) Control within Maintained Centipedegrass Turf. Issue 1 (16th October 2015) - McCurdy, James D.; McElroy, J. Scott; Flessner, Michael L.
Abstract : Common lespedeza or Japanese clover [ Kummerowia striata (Thunb.) Schindl. syn. Lespedeza striata (Thunb.) Hook. & Arn.] is a difficult to control weed in many turf species of the United States. The slow establishment rate, sparse canopy, and low fertility requirements of centipedegrass [ Eremochloa ophiuroides (Munro) Hack.] make this leguminous weed particularly problematic. Additionally, herbicide safety toward centipedegrass can limit postemergence broadleaf herbicide options in warm weather. A 2‐year field study was conducted to evaluate common lespedeza response and centipedegrass turf injury to several available broadleaf herbicides and commercial tank‐mixtures during peak summer conditions. Fluroxypyr (0.47 lb acid equivalent [a.e.]/acre) alone and Escalade 2 (a prepackaged tank‐mixture of 2, 4‐D, fluroxypyr, and dicamba at 1.5 lb a.e./acre) effectively controlled common lespedeza without unacceptable turfgrass injury (≤18%, 2 weeks after treatment). Aminocyclopyrachlor (0.07 and 0.09 lb a.e./acre), which is no longer registered for use within fine turf scenarios, effectively controlled common lespedeza; however, the resulting centipedegrass injury (≥30%, 2 weeks after treatment) would likely be deemed unacceptable in many turfgrass scenarios. This research also highlights several commercially available herbicides routinely used for broadleaf weed control that failed to adequately control common lespedeza.